2005
DOI: 10.1007/s11270-005-2887-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pollutant Content in Road Runoff First Flush Waters

Abstract: Road runoff waters are able to convey a number of organic and inorganic pollutants originated by different non-point sources and by the road surface itself. Such pollutants can enter aquatic systems, thus contributing to water and soil contamination. This study was aimed at evaluating the pollutant content in first flush runoff waters from a highway located in Central Italy. A water sampling apparatus was devised able to collect only the first 10 L of runoff water. Water samples were analyzed by atomic absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 17 publications
0
53
1
1
Order By: Relevance
“…Road-runoff waters: pH=4.0-9.5 (Mangani et al 2005) Eh=0.1-0.8 V (Baas-Becking et al 1960) [Cl]=4 10 4 to 0.2 M (Mangani et al 2005), 0.5 M for snowmelt conditions (Howard & Hayes 1997) The hydroxide species of PGEs may be important in the transport of PGEs emitted by VECs in oxidizing surface environments with Eh-pH conditions similar to those of road-runoff waters, freshwater and soil solutions (Figs. 15b, 16b and 17).…”
Section: Discussionmentioning
confidence: 99%
“…Road-runoff waters: pH=4.0-9.5 (Mangani et al 2005) Eh=0.1-0.8 V (Baas-Becking et al 1960) [Cl]=4 10 4 to 0.2 M (Mangani et al 2005), 0.5 M for snowmelt conditions (Howard & Hayes 1997) The hydroxide species of PGEs may be important in the transport of PGEs emitted by VECs in oxidizing surface environments with Eh-pH conditions similar to those of road-runoff waters, freshwater and soil solutions (Figs. 15b, 16b and 17).…”
Section: Discussionmentioning
confidence: 99%
“…For PC3, it accounted for 12.73 % of the total variance and had strong and positive loadings on DPb and a moderately positive loading on DZn. The Zn and Pb pollution was mainly sourced from vehicle exhaust (Sansalone and Buchberger 1997;Huang et al 2007), but Mangani et al (2005) reported tire wear as a significant source for Zn and Davis et al (2001) and Ball et al (1998) reported that Pb is sourced from lubrication oil and grease. Thus, PC3 mainly results from vehicle emission.…”
Section: Potential Pollution Sourcesmentioning
confidence: 99%
“…These three heavy metals tend to be less particle-bound than other heavy metals such as Pb [6,7]. Sources of Cu in runoff water are brake linings [3,8], metal platings, moving engine parts [9], and pesticides applied to road medians [10]. Ni is present in diesel fuel [1], Ni-Cd batteries, stainless steel, and other electronic equipment [11].…”
Section: Introductionmentioning
confidence: 99%